MORFOMETRIK KIJING TAIWAN (Anodonta woodiana) DI BEBERAPA LOKASI DI KABUPATEN MINAHASA DAN MINAHASA UTARA - Ahazia I. Tampa; Cyska Lumenta; Ockstan J. Kalesaran (Jurnal Ilmiah PLATAX, 2014)
This study was conducted to determine morphometric kijing taiwan at several locations in Minahasa District and North Minahasa regency and its association with the abundance of plankton and water quality. Sampling gravestone taiwan and water quality obtained from the four (4 ) locations: Rap Rap Village, BBAT Tatelu North Minahasa Regency, Paleloan and Tataaran II Village, Minahasa regency. Morphometric measurements kijingg taiwan include dimensional measurements and weighing of the shell. Measurement of shell dimensions include length , width , and thickness. Include the weighing of the weighing of the total, shell weight and wet weight of meat. Water quality measurements carried out directly at the sites include measurement of temperature, pH, dissolved oxygen and water base texture, while the identification of plankton carried in Pathology and Clinical Laboratory of Fish Diseases, Faculty of Fisheries and Marine Sciences, University of Sam Ratulangi. Morphometric measurements will be taken in any of 50 individual kijing taiwan each location. The results of morphometric measurements in multiple locations showed uniform size Tataaran II contained in the Village, the Village and Village Paleloan Rap Rap while in BBAT Tatelu uniformity of size only in size from 7-18 to 9-74 cm was caused by Taiwan in the pool because kijing BBAT Tatelu regarded as pest extermination so regularly done. Relationships shell length and total weight kijing taiwan to change at any time is influenced by several factors such as the condition of gonadal maturation , water quality and availability of food in the waters.